Georgia at the crossroads of economic development - George Abuselidze (ZBW – Leibniz Information Centre for Economics, 2018)
In the last decade of XX century, has expanded the area of capital movements, which included the former socialist countries. Thus, the countries that are attracting some of the centers of the capital and at the same time, participate in the export of capital, it is impossible not to have engaged in a global economy. Our country has been greatly involved in the processes of globalization. At the same time, Georgia's future development will depend on how the country is adapting to globalization with the need for policy implementation, the political, economic and organizational actuating levers. In this regard, the need for more emphasis on the intellectual forces of international finance - financial institutions with their own interests, the use of integrated approaches to economic development, high rates of achievement, social and economic policy harmonization, social inequality mitigation. Finally, the orientation of foreign economic priorities have to be organic in conjunction with the ongoing processes, it must define the strategic objectives of the national economy.
Keywords: F36; H30; E60; 330; Public Finance; Financial Aspects; Economic Integration; Macroeconomic Policy; Fiscal Policy